Еволюція дослідження історії України в ІІІ Речі Посполитій (1989–2018) - Морозова, О. (Історіографічні дослідження в Україні, 2018)
У статті автор аналізує дослідження окремих аспектів історії України в ІІІ Речі Посполитій у руслі загального суспільно-політичного процесу в Польщі. Особлива увага звернена на діяльність польських наукових осередків й окремих істориків, що займаються дослідженням проблем історії України. Автор приходить до висновку, що увага польських істориків здебільшого прикута до т.зв. гострих проблем спільного минулого. Залишаються малодослідженими питання повсякденного життя поляків і українців на південно-східних територіях ІІ Речі Посполитої, культурного і духовного розвитку української спільноти в окреслений період, українсько-польської співпраці на побутовому рівні, проблема національної свідомості українського населення пограниччя тощо. In the article, the author analyzes the evolution of the study of certain aspects of the history of Ukraine in the Third Commonwealth in the context of the general sociopolitical process in Poland. Particular attention is paid to the activities of Polish research centers and individual historians involved in the research on the problems of Ukrainian history. The author comes to the conclusion that the attention of Polish historians is mostly tied to the so-called "Acute problems" of the common past. Issues of the daily life of Poles and Ukrainians in the south-eastern territories of the Second Commonwealth, cultural and spiritual development of the Ukrainian community during the determined period, Ukrainian-Polish co-operation at the domestic level, the problem of national consciousness of the Ukrainian population of the borderland, etc. are still almost not investigated.